Enhancement of Round Trip Time (RTT) and Packet Loss Rate (PLR) in Explicit Rate Adjust (ERA) Protocol - Azamuddin, Abdul Rahman (2010)
Despite the considerable effort of Layered Multicast Protocols (LMPs), the design and implementation of these protocols is still developing. For instance, in the last few years, many researchers are actively involved in designing LMPs. A number of LMPs have been proposed such as, Receiver Layered Multicast (RLM), Receiver Layered Congestion Control (RLC), Packet-pair Cumulative Layered Multicast (PLM), Wave and Equation Based Rate Control (WEBRC), Fair Layer Increase Decrease with Dynamic Layering (FLID-DL), and Adaptive Vegas Multicast Rate Control (AVMRC). However, regardless of the same rationale of the protocol design, the researchers employed different mechanisms for designing their protocols. Explicit Rate Adjustment (ERA) protocol is among the LMPs which are designed to extend the basic control mechanism of the Packet-pair Receiver driven Cumulative Layered Multicast (PLM). The ERA protocol uses the combination of the Transmission Control Protocol (TCP) Equation Model and Packet Pair estimation techniques. Although the ERA protocol has several advantages over the previous LMPs, there are still a number of disadvantages in its design and implementation. The disadvantages include Round Trip Time (RTT) and Packet Loss Rate (PLR) estimation in the TCP- Equation Model. This research focuses on the enhancement of ERA through investigating current research in the design of LMPs. In addition, it involves the simulation and comparison of the performance between the modified ERA and the current ERA protocols. The evaluation criteria conducted by the previous researchers are taken into consideration since each LMP researchers has his/her own method to evaluate the protocols. The simulation results in this study, which have been conducted with NS-2, indicate that modified ERA is better than the current ERA protocol in terms of the following desirable properties: (1)TCP-Friendliness, (2)Smoothness, (3)Stability and (4) Heterogeneity.